Designing Context-Based Digital Comic Video for English for Specific Purposes (ESP) at Vocational High School Tourism Students - Anisa Pinkan Aulia; Ni Putu Artila Dewi; Isyarotullatifah; Kadek Lina Kurniawati (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aimed to design and develop a context-based digital comic video as an English for Specific Purposes (ESP) learning medium to enhance speaking skills among Grade 11 Tourism students at SMK TP 45 Negara, Jembrana, Bali. The research employed a Design and Development (D&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through needs analysis questionnaires, expert validation instruments, teacher response forms, and student practicality questionnaires. The developed media integrates ESP principles, Contextual-Based Learning (CBL), and local Jembrana tourism content. Validity assessment by two material experts yielded a combined score of 85.00% (